PENGARUH KOREAN BRAND AMBASSADOR (BOYBAND BTS) DAN MINAT BELI TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN DI TOKOPEDIA - Alifia Maharani (2022)
The phenomenon of "Korean Wave" is a phenomenon that explains Korean pop culture which has now become a worldwide trend that is in global demand. This Korean Wave then formed an initiation in the field of marketing to attract consumer shopping interest by utilizing the influence of purchasing decisions for consumers using new opportunities from the effects of Korean Brand Ambassadors. This study aims to determine and explain the influence of the Korean Brand Ambassador (Boyband BTS) and purchase intention on the purchase decisions of Tokopedia consumers. This study uses a quantitative descriptive analysis method by distributing questionnaires through Google Form. The research method uses non-probability sampling with purposive sampling of 100 respondents who have the Tokopedia application and are domiciled in Bogor City. The analysis technique used in this research is Partial Least Square (PLS). The results of the study show that (1) the Korean Brand Ambassador (Boyband BTS) has a significant effect on consumer purchasing decisions at Tokopedia with an original sample value of 0.230. (2) Purchase intention has a significant effect on consumer purchasing decisions at Tokopedia with an original sample value of 0.681.